Low plasticity in digestive physiology constrains feeding ecology in diet specialist, Zebra finch (Taeniopygia guttata) - Brzek, Pawel (2009)
It can be hypothesized that species with a wide or variable food niche are able to adjust their digestive physiology to current food type. In diet specialists, however, the capacity for such presumably costly plasticity is not necessary and flexibility of digestive physiology should be lower. Recently, we found that ontogenetic changes in the activity of digestive enzymes in house sparrow, a species that gradually consumes more carbohydrates during ontogeny, are strongly modified by diet composition. In the present study we examined digestive flexibility of nestling and adult zebra finches, typical diet specialists that consume only seeds after hatching. Both adult and nestling zebra finches could not thrive on a protein-rich and carbohydrate-free diet that supported normal development of young house sparrows. Mass-specific activity of intestinal carbohydrases (maltase and sucrase) was not elevated by higher diet carbohydrate content in both nestling and adult birds. Mass-specific activity of maltase changed less during ontogenetic development in zebra finch than in house sparrow. We conclude that the digestive physiology of zebra finch is adapted to process carbohydrate-rich food after hatching and is much less flexible than in house sparrow. We hypothesize that this difference might reflect the lack of a diet switch during ontogeny or result from high specialization to a narrow diet niche.